2009
DOI: 10.1271/bbb.80612
|View full text |Cite
|
Sign up to set email alerts
|

BacteroidesInduce Higher IgA Production ThanLactobacillusby Increasing Activation-Induced Cytidine Deaminase Expression in B Cells in Murine Peyer’s Patches

Abstract: The gut mucosal immune system is crucial in host defense against infection by pathogenic microbacteria and viruses via the production of IgA. Previous studies have shown that intestinal commensal bacteria enhance mucosal IgA production. However, it is poorly understood how these bacteria induce IgA production and which genera of intestinal commensal bacteria induce IgA production effectively. In this study, we compared the immunomodulatory effects of Bacteroides and Lactobacillus on IgA production by Peyer's p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 27 publications
0
25
0
1
Order By: Relevance
“…There are many reports that some probiotic bacteria strains induce IgA production in the intestine. However, not all probiotic strains have the ability to induce production of IgA in vivo , even when the induction of IgA production is confirmed by in vitro studies [13], [33], [34]. It is known that different probiotic strains have different properties and that it is not possible to extrapolate the effects of one probiotic strain to others or the effect of one strain with a specific pathogen to other pathogens [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reports that some probiotic bacteria strains induce IgA production in the intestine. However, not all probiotic strains have the ability to induce production of IgA in vivo , even when the induction of IgA production is confirmed by in vitro studies [13], [33], [34]. It is known that different probiotic strains have different properties and that it is not possible to extrapolate the effects of one probiotic strain to others or the effect of one strain with a specific pathogen to other pathogens [35].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, individuals with IgA deficiency have increased rates of respiratory and gastrointestinal infectious diseases, and lympho-proliferative disorders of the small intestine [9]. It has been reported that intestinal commensal bacteria induce IgA production by developing gut associated lymphoid tissue (GALT) in the small and large intestine [10]–[13]. Within the network of intestinal immunity, dendritic cells (DCs) play a critical role in the switching between stimulating immune regulation or activating immune responses of commensal microbiota [14].…”
Section: Introductionmentioning
confidence: 99%
“…5. Box plots show the percent amino acid identity for metagenomic reads (all 137 metagenomes available at CAMERA, Broad Phage Metagenome, January 2012) recruiting to predicted genes from C. baltica phages (designated as genera [1][2][3][4][5][6][7][8][9][10][11][12], as well as three T4-like phages: marine Prochlorococcus phage P-SSM4 (GenBank accession no. NC_006884), marine Vibrio phage KVP40 (GenBank accession no.…”
Section: Methodsmentioning
confidence: 99%
“…Bacteroidetes bacteria are abundant and active members of bacterial communities in various habitats ranging from Antarctic soil (6) to surface (7) and deep (8) oceans and even the human gut. In humans, Bacteroidetes comprise 30% of the gut microbiota and play important roles for fat storage (9) and the immune system (10). In the oceans, Bacteroidetes is the third most abundant bacterial phylum (7,8), and there these bacteria are active in degrading biopolymers (11) and involved in recycling of phytoplankton bloom-related organic matter (12).…”
mentioning
confidence: 99%
“…oraz inne bakterie Gram-dodatnie o morfologii niciowatej i segmentowanej). Może to sugerować, że na tej drodze bakterie współzawodniczą między sobą i bakterie słabiej indukujące wydzielanie sIgA uzyskują liczbową dominację (35). W obrębie sIgA podklasa sIgA2 jest mniej wrażliwa na degradację przez bakteryjne proteazy.…”
unclassified